Agency at work : an agentic perspective on professional learning and development - Goller, Michael [Herausgeber]; Paloniemi, Susanna [Herausgeber] (Springer, 2017)
"The present book collects, integrates, and discusses the range of perspectives and discourses on agency at work. In addition, the book compiles the empirical research that has been generated by various perspectives. The chapters deal with the relationship between (a) agency at work, and (b) professional learning and development. They encompass a wide variety of working life domains and/or contexts, and are based on a broad range of epistemological and theoretical standpoints. This volume is not only thought to bring together current research, but also to foster the contemporary discourse on workplace agency a few steps further. Although the book strongly focuses on research originating in the field of workplace learning, its contents may be of interest to researchers from other scientific domains, such as socio-cognitive and development psychology, organisational behaviour, leadership, economics, life-course research, and philosophy." (Editor, BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; Lernen am Arbeitsplatz; Kompetenzmodell; Handlungskompetenz; Lebenslanges Lernen; Lernen und Arbeiten; Arbeitswelt